2003
DOI: 10.1021/cm020930c
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of La4Si2O7N2 Analyzed by the Rietveld Method Using the Time-of-Flight Neutron Powder Diffraction Data

Abstract: The polycrystalline single-phase sample of La 4 Si 2 O 7 N 2 was prepared at 1773 and 1873 K by the gas-pressured sintering method. The structure refinement was carried out by the Rietveld method using time-of-flight neutron powder diffraction data measured at 297 K. La 4 Si 2 O 7 N 2 is isostructural with the Y 4 Al 2 O 9 high-temperature phase and crystallizes in a monoclinic cell, P2 1 /c (No. 14-1), Z ) 4. The lattice parameters refined for the sample prepared at 1773 K were a ) 8.0375( 2) Å, b ) 10.9900(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Interatomic La−N/O distances are in the range of 2.41(2)–3.30(2) Å, while Sr/La−N distances vary from 2.62(2) to 3.37(2) Å and Si−N/O distances are between 1.65(1) to 1.77(1) Å and Si−N between 1.64(2) to 1.70(2) Å, which are in good agreement with reported values of other RE − AE −Si−N−O compounds [33–41] . For the substitutional variants RE 8‐ x AE x [Si 10 N 20‐ x O 2+ x ] : Eu 2+ ( RE =La, Ce; AE =Ca, Sr, Ba; 0≤ x ≤2), the mixed occupied sites La/Sr9‐12 can be substituted by Ce and Ca or Ba, respectively, whereas Ca 2+ could also occupy solely La 3+ occupied sites due to similar ionic radii.…”
Section: Resultssupporting
confidence: 90%
“…Interatomic La−N/O distances are in the range of 2.41(2)–3.30(2) Å, while Sr/La−N distances vary from 2.62(2) to 3.37(2) Å and Si−N/O distances are between 1.65(1) to 1.77(1) Å and Si−N between 1.64(2) to 1.70(2) Å, which are in good agreement with reported values of other RE − AE −Si−N−O compounds [33–41] . For the substitutional variants RE 8‐ x AE x [Si 10 N 20‐ x O 2+ x ] : Eu 2+ ( RE =La, Ce; AE =Ca, Sr, Ba; 0≤ x ≤2), the mixed occupied sites La/Sr9‐12 can be substituted by Ce and Ca or Ba, respectively, whereas Ca 2+ could also occupy solely La 3+ occupied sites due to similar ionic radii.…”
Section: Resultssupporting
confidence: 90%
“…Lanthanide oxonitridosilicates are interesting hosts for Ce 3+ . Blue emission is mostly seen in Ce 3+ -doped oxonitridosilicates, with exceptions in La 3 BaSi 5 N 9 O and Y 3 Si 5 N 9 O that emit orange colors. van Krevel et al reported the luminenscence of Ce 3+ in Y–Si–O–N compounds, including YSiO 2 N, Y 5 (SiO 4 ) 3 N, Y 2 Si 3 O 3 N 4 , and Y 4 Si 2 O 7 N 2 .…”
Section: Survey Of Different Types Of Down-conversion Nitride Materialsmentioning
confidence: 99%
“…Among several tricolor phosphors, rare-earth silicon-oxynitrides of Ln 4 Si 2 O 7 N 2 (Ln = Y, Lu, Gd, and La) [6][7][8][9][10] have been found and characterized. The structures of the silicon-oxynitrides typically consist of SiN 4 tetrahedra, and the partial nitrogen of the SiN 4 tetrahedra can be replaced by oxygen to form Si[ON] 4 tetrahedra.…”
Section: Introductionmentioning
confidence: 99%